Hypogean presumably sister species Quedius repentinus sp. n. from Altai and Q. roma from Sikhote-Alin (Coleoptera: Staphylinidae): a disjunct distribution or poorly sampled Siberia? - Salnitska, Maria; Solodovnikov, Alexey (Zootaxa, 2018)
Quedius (Microsaurus) repentinus sp. n., a new hypogean montane talus-associated species from Altai is described and considered sister to the morphologically and bionomically similar Q. (M.) roma Solodovnikov et Hansen, 2016 from Sikhote-Alin. Both species seem more closely related to the Q. (M.) przewalskii species group from the mountains of China than to the Q. (M.) mutilatus species group from Tien-Shan. The identity of Q. (M.) przewalskii Reitter, 1887, a core of the respective species group, is clarified by re-examination of the holotype. The broad gap between the distributions of Quedius repentinus and Q. roma is either a noteworthy biogeographic fact pending explanation, or an artefact resulting from poor sampling pending additional records and new species discovery. Inadequate knowledge of the actual diversity and the distributions of the montane hypogean Quedius of the Russian Asia are illustrated by another new hypogean species from Altai. That species, so far known from a single female only, is here reported but not formally described.